Community structure, diversity and spatial organization of enchytraeids in Mediterranean urban holm oak stands - Rota, Emilia; Caruso, Tancredi; Bargagli, Roberto (European Journal of Soil Biology, 2014)
There is a strong northern bias in Europe as regards enchytraeid community ecology, particularly in urban settings. We approached the enchytraeid assemblages of urban holm oak stands in Naples and Siena adopting a high intensity sampling that, for the first time in the Mediterranean climate zone, would ensure that the data collected be representative of the target populations. Structural parameters (di- versity and evenness, biomass, size classes, aggregation) were compared across different spatial (regional, urban district, within habitat) and temporal scales (season and year). Species richness was found to change significantly only at regional scale; background data suggest that this may depend on the higher environmental heterogeneity occurring at Naples. Differences in size class structure were significant only on a seasonal scale and within either city separately. With one exception (Fridericia bulbosa s.s.), the patterns of spatial aggregation of the common species were fairly robust and the total range of patchiness was consistent with previous studies, despite the different sampling methodologies. The size of the sampling unit, the number of replicates per plot and the number of plots proposed in this study appear suitable to obviate the difficulties of evaluating Mediterranean enchytraeid communities.
Keywords: diversity; Mediterranean climate zone; patchiness; Size class structure; Species biomass; Terrestrial enchytraeids; Urban ecosystems

Strong functional stability of soil microbial communities under semiarid Mediterranean conditions and subjected to long-term shifts in baseline precipitation - Curiel Yuste, J; Fernandez-Gonzalez, a.J. J; Fernandez-Lopez, M; Ogaya, R; Penuelas, J; Sardans, J; Lloret, F (Soil Biology and Biochemistry, 2014)
Abstract We investigated the effect of soil microclimate on the structure and functioning of soil microbial communities in a Mediterranean Holm-oak forest subjected to 10 years of partial rain exclusion manipulations, simulating average drought conditions expected in Mediterranean areas for the following decades. We applied a high throughput DNA pyrosequencing technique coupled to parallel measurements of microbial respiration (RH) and temperature sensitivity of microbial respiration (Q10). Some consistent changes in the structure of bacterial communities suggest a slow process of community shifts parallel to the trend towards oligotrophy in response to long-term droughts. However, the structure of bacterial communities was mainly determined by short-term environmental fluctuations associated with sampling date (winter, spring and summer) rather than long-term (10 years) shifts in baseline precipitation. Moreover, long-term drought did not exert any chronic effect on the functioning of soil microbial communities (RH and Q10), emphasizing the functional stability of these communities to this long-term but mild shifts in water availability. We hypothesize that the particular conditions of the Mediterranean climate with strong seasonal shifts in both temperature and soil water availability but also characterized by very extreme environmental conditions during summer, was acting as a strong force in community assembling, selecting phenotypes adapted to the semiarid conditions characterizing Mediterranean ecosystems. Relations of climate with the phylogenetic structure and overall diversity of the communities as well as the distribution of the individual responses of different lineages (genera) to climate confirmed our hypotheses, evidencing communities dominated by thermotolerant and drought-tolerant phenotypes.
Keywords: Adaptation; CO2; diversity; Extreme events; functional stability; Mediterranean climate; Soil bacterial communities

Designing bryophyte surveys for an optimal coverage of diversity gradients - Medina, Nagore G; Lara, Francisco; Mazimpaka, Vicente; Hortal, Joaquin (BIODIVERSITY AND CONSERVATION, 2013)
Knowledge on the distribution and abundance of species is plagued by significant taxonomic and geographic biases that influence the analyses on biodiversity patterns. Due to this, standard, easy-to-use methods are needed to design efficient field campaigns that minimize data deficiencies. We evaluate the applicability, usefulness and effectiveness of a survey design protocol based on the Environmental Diversity (ED) criterion under different scenarios, with examples of varying extent of environmental niche, range of spatial distribution and level of previous knowledge. We planned surveys for epiphytic bryophytes growing in three types of forests at NW Iberian Peninsula (dominated by Quercus ilex, Q. faginea and Q. pyrenaica). Knowledge on the distribution and abundance of epiphytic bryophytes in this region presents large gaps and strong geographic biases. Besides, the three forest types differ in their environmental requirements, spatial distribution and level of previous knowledge, providing three working scenarios to test the response of the protocol under different situations. The protocol was implemented as a set of sequential selection rules, starting by an ED-based criterion aiming at maximizing the coverage of climatic and geographic variability; further criteria include an iterative set of qualitative properties: maximizing forest area, conservation status and accessibility. The protocol performed efficiently at different ranges of spatial distribution levels of environmental variability, and degree of previous knowledge and generated an even distribution of sampling points that efficiently covered the diversity of epiphytic bryophytes. The results show that ED protocols are a proficient and time-saving approach to select sampling sites by objective criteria also for groups with high dispersal ability and fragmented landscapes.
Keywords: diversity; ED protocol; epiphytic bryophytes; Mediterranean; method; p-Median; Quercus forests; Sampling design

Impact of targeted sheep grazing on herbage and holm oak saplings in a silvopastoral wildfire prevention system in south-eastern Spain - Ruiz-Mirazo, Jabier; Robles, Ana Belén (Agroforestry Systems, 2012)
Several wildﬁre prevention programs in southern Europe are currently using livestock grazing for the maintenance of fuelbreaks. This silvopastoral management is valued for being sustainable and effective in reducing fuel loads, but few studies have analyzed other impacts linked to fuelbreak grazing. This paper reports on an experiment performed within the wildﬁre prevention program in Andalusia (southern Spain) with the aim of clarifying and quantifying the effect of fuelbreak grazing on herbage biomass, ground cover, herbage species composition, and growth of holm oak saplings. The study site, located in a semiarid Mediterranean environment, was grazed by a shepherded sheep ﬂock from February to June in three consecutive years at a similar stocking rate. Livestock consumed between 33 and 68 % of herbage production in the different years, and the greatest fuel reduction (remaining dry matter of 200 kg ha -1 ) was registered in Year 2, when rainfall and herbage production was lowest. Ground cover was signiﬁ- cantly affected by grazing: on average, the percentage of bare soil increased three-fold, while herbage cover was reduced by a quarter. The botanical composition of herbage varied remarkably between years, but very little between Grazed and Non-Grazed areas within each year. Non-browsed holm oak saplings became progressively larger than browsed ones, differences only reaching clear statistical signiﬁcance at the end of the three experimental years. At this time, the volume of browsed saplings was 47–56 % smaller than that of non-browsed holm oaks, even though the former had also grown signiﬁcantly in the course of the experiment.
Keywords: biomass; diversity; Grazed fuelbreak; Ground cover; Mediterranean; semiarid

Quercus calliprinos regrowth advantage under grazing in Mediterranean maquis and its management implications - Agra, Har’el; Ne’eman, Gidi (Forest Ecology and Management, 2011)
The post disturbance natural succession of the Mediterranean maquis, which turns open and species-rich landscapes into dense, closed stands of sclerophyllous woody vegetation is a principal threat to plant and animal diversity. Therefore, in the absence of traditional agricultural disturbance, active management regimes that include cutting and grazing are proposed to preserve biodiversity. The Mediterranean woody vegetation in Israel is strongly dominated by one species – the evergreen sclerophyllous Quercus calliprinos (Kermes oak). We hypothesized that under cutting and grazing, the evergreen Q. calliprinos has a relative regrowth advantage over other competing tree species. Here we examined the effect of grazing and the effect of tree structural traits on the regrowth after clear cutting of all trees in our study plots at Mt. Meron LTER site, Israel. All trees were removed from ﬁve blocks of 2000 m2 and each block was divided into two plots, ﬁve of which were exposed to grazing livestock while ﬁve were wire-fenced and ungrazed. The regrowth rate of Q. calliprinos under grazing was higher than that of all other tree species suggesting that in the long-term, under such a conservation management regime, the dominance of the evergreen sclerophyllous Q. calliprinos over the deciduous tree species will increase and consequently will decrease plant and animal diversity. Therefore, we conclude that to protect landscape and species diversity in Mediterranean ecosystems dominated by evergreen oaks, when cutting and grazing are applied, special care must be paid to trees that are more negatively affected by such treatment.
Keywords: Deciduous trees; diversity; Evergreen trees; Grazing; Regrowth; Sclerophyllous vegetation

Diversity of soil basidiomycete communities associated with Quercus suber L. in Portuguese montados - Barrico, Lurdes; Rodríguez-Echeverría, Susana; Freitas, Helena (European Journal of Soil Biology, 2010)
The montado is an agro-silvo pastoral system characterized by an open oak formation combined with shrubs or a rotation of cultures/pastures/fallow. A key, but frequently overlooked, component of these systems is the fungal community associated with the dominant oaks. We present a study of the basidiomycete community in montado areas of Quercus suber L. from Central-Western Portugal, based on fruiting body assessment and PCR-DGGE of soil mycelium. Soil available phosphorus and organic matter content were also determined. The most frequent fruiting body found in the cork oak montados belonged to Lactarius, Clitocybe, Russula and Cortinarius species. Lactarius chrysorrheus was the most widely distributed species. Soil management practices cause a temporal increase in soil available phosphorus, and harrowing and fertilizer application also result in an increase in soil organic matter content. Mechanical clearing with recent soil disturbance had a negative effect on the richness and diversity of the basidiomycete community assessed using fruiting body. The molecular analysis of the basidiomycete community separated the sites with recent shrub-removal from the others sites. Our results show that soil management techniques that avoid disturbance of the top-soil layers are the best way to preserve the structure and diversity of the soil fungal community in the montado.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: Basidiomycete; Dehesa; dgge; diversity; montado

Mycorrhizal macrofungi diversity (Agaricomycetes) from Mediterranean Quercus forests; a compilation for the Iberian Peninsula (Spain and Portugal) - Ortega, Antonio; Lorite, Juan; Valle, Francisco (Nova Hedwigia, 2010)
A compilation study has been made of the mycorrhizal Agaricomycetes from several sclerophyllous and deciduous Mediterranean Quercus woodlands from Iberian Peninsula. Firstly, we selected eight Mediterranean taxa of the genus Quercus, which were well sampled in terms of macrofungi. Afterwards, we performed a database containing a large amount of data about mycorrhizal biota of Quercus. We have defined and/or used a series of indexes (occurrence, affinity, proportionality, heterogeneity, similarity, and taxonomic diversity) in order to establish the differences between the mycorrhizal biota of the selected woodlands. The 605 taxa compiled here represent an important amount of the total mycorrhizal diversity from all the vegetation types of the studied area, estimated at 1,500-1,600 taxa, with Q. ilex subsp. ballota (416 taxa) and Q. suber (411) being the richest. We also analysed their quantitative and qualitative mycorrhizal flora and their relative richness in different ways: woodland types, substrates and species composition. The results highlight the large amount of mycorrhizal macrofungi species occurring in these mediterranean Quercus woodlands, the data are comparable with other woodland types, thought to be the richest forest types in the world. We point out that the presence of genera that are very well adapted to sclerophyllous Mediterranean woodlands with a potential use in afforestation or recovery programs, or being rare species, are listed in the Regional Red List of Endangered Macromycetes. Since, these woodlands suffer heavy environmental pressure, human and climate mediated, we conclude many species are approaching a high extinction risk, and it is urgent to apply legal and management measures, both, of national (Spain and Portugal) and European governments.
The following values have no corresponding Zotero field: pub-location: Stuttgart publisher: Schweizerbart'sche Verlagsbuchhandlung
Keywords: affinity; conservation; diversity; mycorrhizal macrofungi; quercus woodlands

Diversité floristique des suberaies du Parc National de Tlemcen (Algerie - Letreuch-Belarouci, A. (Acta botánica malacitana, 2009)
The analysis of the ﬂoristic diversity of forest massif “Haﬁr-Zariffet” in the Tlemcen National Park has revealed the existence of 211 taxa which belong to 65 families and 164 genera. The number of taxa endemic and/or rare includes: 1 endemic algerian, 7 algero-moroccan, 11 ibero-algero-moroccan, 7 are endemic in North Africa and 11 are endemic in Iberian Peninsula and North Africa. The number of rare taxa is 26, 9 are at the same time threatened. Urgent efforts are required to preserve the cork oak as well as endemic species conﬁned to it.
Keywords: Algeria; Cork Oak Forest; diversity; Inventory; national park of tlemcen

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi as indicators of land-use severity in managed woodlands dominated by Quercus suber — a case study from southern Portugal - Azul, Anabela Marisa; Castro, Paula; Sousa, José Paulo; Freitas, Helena (Canadian Journal of Forest Research, 2009)
We assessed the impacts of current management practices used to control shrub strata in Portuguese oak woodlands dominated by Quercus suber L. (montado) on fruiting diversity and abundance of ectomycorrhizal-forming fungi (ECMF) and saprobic fungi. Fruit bodies were collected over four fruiting seasons in 16 plots (20 m × 20 m) selected in a montado landscape with extensive silvopastoral exploitation. A total of 9484 fruit bodies were found in 171 taxa (74 ECMF, 96 saprobic, and 1 parasitic). Our results show that shrub density control by permanent grazing or by cutting practices followed by soil tillage leads to lower fruiting production and greater changes in taxa composition, particularly for ECMF fruit bodies, than cutting practices without soil tillage. Principal response curve analysis showed that ECMF reacted more sensitively to these practices, in particular Laccaria laccata, Hebeloma cistophilum, Russula cyanoxantha, Cortinarius trivialis, and Lactarius volemus. We also observed that shrub cutting without soil tillage allowed ECMF fruiting to recover to predisturbance levels after 3 years. Our data imply that fruit bodies were useful indicators for assessing the severity of the effects of different land-use practices applied in montado areas on soil fungal populations.
doi: 10.1139/X09-148doi: 10.1139/X09-148The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: diversity; fruiting patterns; fungi; montado (voyant); shrub management; Tillage

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi as indicators of land-use severity in managed woodlands dominated by Quercus suber — a case study from southern Portugal - Azul, Anabela Marisa; Castro, Paula; Sousa, José Paulo; Freitas, Helena (Canadian Journal of Forest Research, 2009)
We assessed the impacts of current management practices used to control shrub strata in Portuguese oak woodlands dominated by Quercus suber L. (montado) on fruiting diversity and abundance of ectomycorrhizal-forming fungi (ECMF) and saprobic fungi. Fruit bodies were collected over four fruiting seasons in 16 plots (20 m × 20 m) selected in a montado landscape with extensive silvopastoral exploitation. A total of 9484 fruit bodies were found in 171 taxa (74 ECMF, 96 saprobic, and 1 parasitic). Our results show that shrub density control by permanent grazing or by cutting practices followed by soil tillage leads to lower fruiting production and greater changes in taxa composition, particularly for ECMF fruit bodies, than cutting practices without soil tillage. Principal response curve analysis showed that ECMF reacted more sensitively to these practices, in particular Laccaria laccata, Hebeloma cistophilum, Russula cyanoxantha, Cortinarius trivialis, and Lactarius volemus. We also observed that shrub cutting without soil tillage allowed ECMF fruiting to recover to predisturbance levels after 3 years. Our data imply that fruit bodies were useful indicators for assessing the severity of the effects of different land-use practices applied in montado areas on soil fungal populations.
doi: 10.1139/X09-148
Keywords: diversity; fruiting patterns; fungi; montado (voyant); shrub management; Tillage

Patterns of species impoverishment in managed forests of Catalonia (NE Spain) - Lloret, F.; Solé, A.; Pino, J. (Journal of Vegetation Science, 2009)
Question: In managed forests, woody plant richness shows great variations in pattern. Herein we try to elucidate the role of major factors, such as successional status, to explain this variation. Assuming that less competitive or disturbance-sensitive species will be systematically more prone to disappear, we investigate the existence of nonrandom patterns of species impoverishment – i.e., the number of species unable to attain maximal richness – and the ecological and successional status of species associated with impoverishment in relation to a regional climatic gradient. Methods: We explored species composition in approximately 7500 forest plots in Catalonia (NE Spain). We evaluated non-random patterns of species impoverishment by analyzing their nestedness. Multivariate analysis was used to relate environmental variables and impoverishment to species occurrence. Plot successional status and ecological range were also estimated from species composition, and species impoverishment was then correlated to these estimators. Results: Most forests show a non-random pattern of species loss: poor stands tend to retain the same species, and the species determining high richness tend to be the same. Late successional species tend to be more common in impoverished plots of drier and warmer forests, while species typical of open or disturbed habitats are more common in impoverished plots of moister and colder forests. Communities dominated by early or late successional species are mostly impoverished, while the richest stands are constituted by species of intermediate stages. Forests dominated by species with a narrow or wide ecological range showed high impoverishment levels, while the richest stands had species with an intermediate ecological range. Discussion: In warmer Mediterranean forests, impoverishment tends to be associated with late successional stages, while in moister and colder forests, species loss is more closely related to disturbance and exploitation. This study reveals the difﬁculties involved in using species richness as a simple descriptor of the degree of forest conservation. Identiﬁcation of dominant species and species indicative of ecological processes would constitute an easily applicable practice that would consolidate assessment of forests status.
Keywords: diversity; Forest management; nestedness; Species composition; Species richness; succession

Dictyostelids from Mediterranean forests of the south of Europe - Romeralo, María; Lado, Carlos (Mycological Progress, 2006)
The first results of a study of dictyostelid diversity in soils of Mediterranean vegetation are presented. Surface soil samples were collected during 2003–2004 from different Mediterranean forests in Spain and Portugal and were plated out for cellular slime moulds. Isolated during this study were 14 species of dictyostelids. One species, Dictyostelium firmibasis is reported for the first time from Europe, and nine (Dictyostelium aureo-stipes, Dictyostelium sp. 1, Dictyostelium fasciculatum, Dictyostelium giganteum, Dictyostelium implicatum, Dictyostelium leptosomum, Dictyostelium sphaerocephalum, Polysphondylium candidum, Polysphondylium pallidum) are new records for the Mediterranean region. Members of the three genera Dictyostelium (ten species), Polysphondylium (three species) and Acytostelium (one species) are present in this region of the world. Comments on their diversity and distribution are included.
Keywords: Dictyostelids; distribution (PG); diversity; mediterranean forest soils

Dictyostelids from Mediterranean forests of the south of Europe - Romeralo, María; Lado, Carlos (Mycological Progress, 2006)
The first results of a study of dictyostelid diversity in soils of Mediterranean vegetation are presented. Surface soil samples were collected during 2003–2004 from different Mediterranean forests in Spain and Portugal and were plated out for cellular slime moulds. Isolated during this study were 14 species of dictyostelids. One species, Dictyostelium firmibasis is reported for the first time from Europe, and nine (Dictyostelium aureo-stipes, Dictyostelium sp. 1, Dictyostelium fasciculatum, Dictyostelium giganteum, Dictyostelium implicatum, Dictyostelium leptosomum, Dictyostelium sphaerocephalum, Polysphondylium candidum, Polysphondylium pallidum) are new records for the Mediterranean region. Members of the three genera Dictyostelium (ten species), Polysphondylium (three species) and Acytostelium (one species) are present in this region of the world. Comments on their diversity and distribution are included.
Keywords: Dictyostelids; distribution (PG); diversity; mediterranean forest soils

Forest structure and understory diversity in Quercus pyrenaica communities with different human uses and disturbances - Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Taboada, Ángela (Forest Ecology and Management, 2006)
The aim is to compare the diversity of the understory in Quercus pyrenaica communities according to the type of human intervention (grazing, obtaining wood or ﬁrewood, forest ﬁres). This interaction results in a modiﬁcation of the characteristics of the arboreal layer and shrub cover. Four types of oak communities were selected, each with ﬁve replicates: communities with a high density of shrubby oak (oak shrublands), open woodlands (‘‘dehesas’’), mature oak woods with abundant woody biomass in the understory and mature oak woods with little woody biomass in the understory. In each study site, we quantiﬁed the size of the trees (height, trunk perimeter and crown diameter) and their density, woody cover in the understory and species richness as well as diversity using the Shannon index, on both a small scale (per m 2 ) and for the total of each community. A clear difference was observed between the dehesas and the oak shrublands, the two community types with higher human intervention (the dehesas, with sustainable use for grazing and the oak shrublands, the most degraded due to repeated ﬁres), in the principal components analysis carried out with these variables. The other two community types, considered more mature forests, presented an intermediate location on the principal components analysis. However, there was no clear relationship between the different community types and the diversity values. No differences were observed in total species richness, except that the number of annuals being signiﬁcantly higher in the dehesas. Nor was it possible to detect any differences using the Shannon index, except for the oak shrublands which, although with a great variability among them, had a lower mean diversity than the other community types. The distance between trees was positively correlated to diversity, measured using the Shannon index, and to annual species richness and negatively correlated to woody cover in the understory. The variability in the distance between trees (associated with clumped distributions) was positively correlated to spatial heterogeneity, measured as Sb. The size of the trees had very little correlation to species diversity. As a whole, the results obtained show the difﬁculty involved in making generalised conclusions on the effects of disturbances on plant diversity
Keywords: annuals; Density; diversity; human intervention; land-use history; Oak trees; perennial herbs; Quercus pyrenaica; size; woody species

Forest structure and understory diversity in Quercus pyrenaica communities with different human uses and disturbances - Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Taboada, Ángela (Forest Ecology and Management, 2006)
The aim is to compare the diversity of the understory in Quercus pyrenaica communities according to the type of human intervention (grazing, obtaining wood or ﬁrewood, forest ﬁres). This interaction results in a modiﬁcation of the characteristics of the arboreal layer and shrub cover. Four types of oak communities were selected, each with ﬁve replicates: communities with a high density of shrubby oak (oak shrublands), open woodlands (‘‘dehesas’’), mature oak woods with abundant woody biomass in the understory and mature oak woods with little woody biomass in the understory. In each study site, we quantiﬁed the size of the trees (height, trunk perimeter and crown diameter) and their density, woody cover in the understory and species richness as well as diversity using the Shannon index, on both a small scale (per m 2 ) and for the total of each community. A clear difference was observed between the dehesas and the oak shrublands, the two community types with higher human intervention (the dehesas, with sustainable use for grazing and the oak shrublands, the most degraded due to repeated ﬁres), in the principal components analysis carried out with these variables. The other two community types, considered more mature forests, presented an intermediate location on the principal components analysis. However, there was no clear relationship between the different community types and the diversity values. No differences were observed in total species richness, except that the number of annuals being signiﬁcantly higher in the dehesas. Nor was it possible to detect any differences using the Shannon index, except for the oak shrublands which, although with a great variability among them, had a lower mean diversity than the other community types. The distance between trees was positively correlated to diversity, measured using the Shannon index, and to annual species richness and negatively correlated to woody cover in the understory. The variability in the distance between trees (associated with clumped distributions) was positively correlated to spatial heterogeneity, measured as Sb. The size of the trees had very little correlation to species diversity. As a whole, the results obtained show the difﬁculty involved in making generalised conclusions on the effects of disturbances on plant diversity
Keywords: annuals; Density; diversity; human intervention; land-use history; Oak trees; perennial herbs; Quercus pyrenaica; size; woody species

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Genetic diversity of European populations of the oak fine-root pathogen Phytophthora quercina - Cooke, D E L; Jung, T; Williams, N a.; Schubert, R; Osswald, W; Duncan, J M (Forest Pathology, 2005)
The recently discovered oak-specific fine root plant pathogen Phytophthora quercina is a significant factor in the current phase of European oak decline but its origins and ecology are poorly understood. A genome-wide analysis of 260 amplified fragment length polymorphism (AFLP) markers was used to examine the genetic diversity of 72 isolates from five oak species at 28 sites in Germany (particularly Bavaria), Italy, France, Hungary and the UK. Within-site diversity was examined at 16 sites. The limited genetic diversity (within and between sites) and lack of genetic substructuring according to geographic origin or host species suggest the rapid spread of a relatively recently introduced species. Two subgroups were distinguished and these may reflect an initial introduction of isolates of two different genetic backgrounds. The relatively low genetic diversity is probably because of the predominantly inbreeding (homothallic) nature of P. quercina. However, evidence of limited intra-site diversity, temporal variation and the lack of clonality within the European population suggest that some diversity is being maintained by occasional outcrossing and turnover of a reservoir of long-lived soil-borne oospore (sexually derived) inoculum
Keywords: AFLP; decline; diversity; pathogen (voyant); Phytophthora

Genetic diversity of European populations of the oak fine-root pathogen Phytophthora quercina - Cooke, D. E. L.; Jung, T.; Williams, N. a; Schubert, R.; Osswald, W.; Duncan, J. M. (Forest Pathology, 2005)
The recently discovered oak-specific fine root plant pathogen Phytophthora quercina is a significant factor in the current phase of European oak decline but its origins and ecology are poorly understood. A genome-wide analysis of 260 amplified fragment length polymorphism (AFLP) markers was used to examine the genetic diversity of 72 isolates from five oak species at 28 sites in Germany (particularly Bavaria), Italy, France, Hungary and the UK. Within-site diversity was examined at 16 sites. The limited genetic diversity (within and between sites) and lack of genetic substructuring according to geographic origin or host species suggest the rapid spread of a relatively recently introduced species. Two subgroups were distinguished and these may reflect an initial introduction of isolates of two different genetic backgrounds. The relatively low genetic diversity is probably because of the predominantly inbreeding (homothallic) nature of P. quercina. However, evidence of limited intra-site diversity, temporal variation and the lack of clonality within the European population suggest that some diversity is being maintained by occasional outcrossing and turnover of a reservoir of long-lived soil-borne oospore (sexually derived) inoculum
Keywords: AFLP; decline; diversity; pathogen (voyant); Phytophthora

Richesse et diversité floristique de la suberaie de la Mamora (Maroc) - Aafi, Abderrahman; KADMIRI, A. A. E. L. (Acta Botanica Malacitana, 2005)
The survey aims to quantify the floristic richeness and diversity of the Mamora’s forest oak-cork ecosystem on the basis of transects and floristic samples distributed according to a stratified and systematic sampling in the different plant formations previously distinguished. The results show that the ecosystem contains 62 families, 261 genders, 408 species, subspecies and varieties : 35 very rare taxa , 29 rare taxa ; 18 endemic taxa, 1 very rare and endemic taxa and 4 rare and endemic taxa. The survey has, otherwise, permitted to reveal the total disappearance of Erica arborea and E. scoparia from this ecosystem and to define the biological spectrum of the studied region, wich is characterized with a clear dominance of therophytes (50.5%).
Keywords: diversity; Mamora; Morocco; Quercus suber; richeness

Richesse et diversité floristique de la suberaie de la Mamora (Maroc) - Aafi, Abderrahman; KADMIRI, A A E L (Acta Botanica Malacitana, 2005)
The survey aims to quantify the floristic richeness and diversity of the Mamora’s forest oak-cork ecosystem on the basis of transects and floristic samples distributed according to a stratified and systematic sampling in the different plant formations previously distinguished. The results show that the ecosystem contains 62 families, 261 genders, 408 species, subspecies and varieties : 35 very rare taxa , 29 rare taxa ; 18 endemic taxa, 1 very rare and endemic taxa and 4 rare and endemic taxa. The survey has, otherwise, permitted to reveal the total disappearance of Erica arborea and E. scoparia from this ecosystem and to define the biological spectrum of the studied region, wich is characterized with a clear dominance of therophytes (50.5%).
Keywords: diversity; Mamora; Morocco; Quercus suber; richeness

Biodiversity of woody species in oak woodlands of southern Spain and northern Morocco - MARAÑÓN, T; Ajbilou, R; Ojeda, F; Arroyo, J (Forest Ecology and Management, 1999)
Three biodiversity parameters ± species richness, endemic species richness and taxonomic singularity ± have been evaluated for the woody understorey of oak woodlands on sandstone-derived substrates, on both sides of the Strait of Gibraltar. There is a similarity in ¯oristic composition and ecological distribution of woody plant communities across the Strait. Nevertheless, we have detected signi®cant differences. These include a general reduction in species richness, number of endemic species and taxonomic singularity (at the community level), and a greater abundance of widespread, generalist species, on the southern side (Moroccan) communities, as compared to the north (Spanish ones). We interpret these differences as partly caused by the contrasting management of woodlands, with higher slashing and browsing pressure in Morocco.
Keywords: Cork oak; diversity; Mediterranean woodlands; Quercus; Species richness; strait of gibraltar

Diversity and structure of ant communities associated with oak, pine, eucalyptus and arable habitats in Portugal - Cammell, M E; Way, M J; Paiva, M R (Insectes Sociaux, 1996)
In central Portugal, 28 species of ants were found in oak, 25 in pine, 35 in eucalyptus and 12 in arable habitats, a total of 43 species. They include five numerically dominant species, the exotic Argentine ant. Linepithema (Iridomyrmex) humile and four native species, Crematogaster scutel- laris, Pheidole pallidula, Tapinoma nigerrimum and Tetramorium hispanicum. L. humile occurred in 34 % of sampled sites. When present, it was abundant in all three arboreal habitats, where it was associated with strikingly decreased ant species richness and equitability. Such diversity was greater in L. humile - colonised arable habitats, where the ant was much less abundant than in the arboreal habitats. Where L. humile was absent, C. scutellaris and P pallidula were usually co-dominants in oak and pine, and T. nigerrimum and T. hispanicum in the arable habitat, but all were absent or rare in eucalyptus. Ants were numerically least abundant in eucalyptus but, in the absence of L. humile, species richness was greater and the community more equitable than in the other habitats. L. humile - absent arable habitats supported the poorest and least equitable ant community.
Keywords: Ants; community ecology; diversity; Dominance; Linepithema humile; Portugal.

Diversity and structure of ant communities associated with oak, pine, eucalyptus and arable habitats in Portugal - Cammell, M. E.; Way, M. J.; Paiva, M. R. (Insectes Sociaux, 1996)
In central Portugal, 28 species of ants were found in oak, 25 in pine, 35 in eucalyptus and 12 in arable habitats, a total of 43 species. They include five numerically dominant species, the exotic Argentine ant. Linepithema (Iridomyrmex) humile and four native species, Crematogaster scutel- laris, Pheidole pallidula, Tapinoma nigerrimum and Tetramorium hispanicum. L. humile occurred in 34 % of sampled sites. When present, it was abundant in all three arboreal habitats, where it was associated with strikingly decreased ant species richness and equitability. Such diversity was greater in L. humile - colonised arable habitats, where the ant was much less abundant than in the arboreal habitats. Where L. humile was absent, C. scutellaris and P pallidula were usually co-dominants in oak and pine, and T. nigerrimum and T. hispanicum in the arable habitat, but all were absent or rare in eucalyptus. Ants were numerically least abundant in eucalyptus but, in the absence of L. humile, species richness was greater and the community more equitable than in the other habitats. L. humile - absent arable habitats supported the poorest and least equitable ant community.
Keywords: Ants; community ecology; diversity; Dominance; Linepithema humile; Portugal.

Differences between oligotrophic communities resulting from old-field succession in relation to bedrock - Puerto, A.; Rico, M. (Plant Ecology, 1994)
Dehesa ecosystems on granite and on slate clearly differ in soil characteristics. Our aim was to find out whether floristic composition differed too. We selected an equal number of plots, on both granite and slate, in different successional stages of development and at various ages after field abandonment (the youngest 15-20 years). Plots with rock-outcrops, which had never been cultivated, were also included in the study. The results showed that floristic differences between granite and slate communities were not detectable in the younger successional stages. However, they showed up with time and on stabilized grasslands became significant. But on plots with rock-outcrops the differences were not observable. This was undoubtedly influenced by the peculiar features of these plots, characterised by poor arid soils and surface parent material. In fact they did not show significant differences in the analysed soil parameters either. Species diversity and biomass showed a similar pattern of differences to floristic composition. The highest species diversity was found on plots with lower biomass (the youngest ones). The lowest biomass in conjunction with quite low species diversity was found on plots with rock-outcrops, which again is consistent with their peculiar features.
Keywords: biomass; diversity; granite; mediterranean grasslands; slate

Differences between oligotrophic communities resulting from old-field succession in relation to bedrock - Puerto, A; Rico, M (Plant Ecology, 1994)
Dehesa ecosystems on granite and on slate clearly differ in soil characteristics. Our aim was to find out whether floristic composition differed too. We selected an equal number of plots, on both granite and slate, in different successional stages of development and at various ages after field abandonment (the youngest 15-20 years). Plots with rock-outcrops, which had never been cultivated, were also included in the study. The results showed that floristic differences between granite and slate communities were not detectable in the younger successional stages. However, they showed up with time and on stabilized grasslands became significant. But on plots with rock-outcrops the differences were not observable. This was undoubtedly influenced by the peculiar features of these plots, characterised by poor arid soils and surface parent material. In fact they did not show significant differences in the analysed soil parameters either. Species diversity and biomass showed a similar pattern of differences to floristic composition. The highest species diversity was found on plots with lower biomass (the youngest ones). The lowest biomass in conjunction with quite low species diversity was found on plots with rock-outcrops, which again is consistent with their peculiar features.
Keywords: biomass; diversity; granite; mediterranean grasslands; slate

Mediterranean evergreen oak diversity: morphological and chemical variation of acorns - Afzal-Rafii, Zara; Dodd, Richard S.; Pelleau, Yvonne (Canadian Journal of Botany, 1992)
Acorns of mediterranean evergreen oak were collected from eight ecogeographically contrasting localities in Italy and Spain. Biometrical analysis of acorns and their cupules showed much greater variation among Spanish populations, encompassing the variation in Italy. The Spanish population at El Pardo, considered the type locality for Quercus rotundifolia, separated from all others. Multivariate analyses of the chemical data indicated, on the one hand, separation of Spain from Italy, and on the other hand, a separation of interior Spanish populations from coastal populations. The importance of lipid composition in the former separation may reflect genetic differentiation between these two origins. Coastal populations were closer to Italian and we suggest were a zone of introgression and hybridization between Quercus ilex and Q. rotundifolia and probably also Quercus coccifera at Bonete Albacete
doi: 10.1139/b92-184doi: 10.1139/b92-184The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: biometry; chemistry; diversity; ecogeography; Quercus ilex; Quercus rotundifolia

Space-time variability in mediterranean pastures analyzed with diversity parameters - Pablo, C L; Peec, B; Galiano, E F; Nicolas, J P; Pineda, F D (Plant Ecology, 1982)
Different parameters of diversity and spatial niche amplitude (Pielou, 1975, Pineda et aL, 1981 b) have been used to describe the spatial organization of mediterranean grasslands in Central Spain. A slope sampled by 480 contiguous 8 X 8 cm quadrats proved to have a homogeneous floristic distribution when it was divided into 160 parts and maximum heterogeneity when divided into 4 sectors. These sectors corresponded to different geomorphological zones of the slope. The complexity of vegetation distribution on the slope was reflected by differences in organization - measured by diversity parameter A = H ( P / E ) / l o g a N (number of plots) between the parts obtained by division. The presence of low-entropy species - specialists - and high entropy species - generalists - was related to the different scales of slope organization. The spatial distribu- tion of plants was compared for different successional stages. Multivariate analysis of sampling plots confirmed previously identified organizational characteristics and clarified the nature of transitions between communities of different floristic composition or structure.
Keywords: diversity; geomorphology; grassland; spatial organization; succession